An unusual case of breathlessness. Issue 1 (March 2021) - Ur Rasool, Masood; Nadeem, Iftikhar; Khatana, Usman Feroze; Hand, Sadiyah
A 39-year-old advanced nurse practitioner in the accident and emergency department presented with influenza-like symptoms, shortness of breath, cough, fatigue and generalised arthralgia. Her cough was non-productive and nocturnal in nature. There was no history of fever, chest pain, haemoptysis, night sweats, weight loss or joint swelling. We present the case of an asthmatic patient who continued to present with breathlessness and received multiple courses of steroids for her presumed asthma exacerbations. After multiple investigations, we made the diagnosis of TBM secondary to relapsing polychondritis. https://bit.ly/3b8Uw1O